2010
DOI: 10.1021/jp105390c
|View full text |Cite
|
Sign up to set email alerts
|

A G3 Study of the Structure of Carbon−Nitrogen Nanoclusters

Abstract: Possible structures of the carbon-nitrogen clusters of the form C(m)N(n) (m = 1-4, n = 1-4, m + n = 2-5) were predicted for the neutral, anion, and cation species in the singlet, doublet, and triplet states, whenever appropriate. The calculations were performed at the G3, MP2(fc)/6-311+G*, and B3LYP/6-311+G* levels of theory. Several molecular properties related to the experimental data--such as the electronic energy, equilibrium geometry, binding energy, HOMO-LUMO gap (HLG), and spin contamination --wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 80 publications
2
5
0
Order By: Relevance
“…Density functional theory (DFT) computations performed by Pascoli and Lavendi then revealed linear (N‐terminated) geometries for all the investigated C 2 n −1 N − ( n= 2–4) and C 2 n N − ( n= 1–3) anions with singlet ( 1 Σ + ) and triplet ( 3 Σ − ) ground states, respectively. More recent theoretical investigations of various C n N m species of different spin state and charge support the results of the DFT computations . For C 4 N − , an electronically closed‐shell singlet 1 A 1 excited state with a branched, kite‐like structure of C 2 v symmetry is predicted +15 kJ mol −1 above the 3 Σ − ground state.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Density functional theory (DFT) computations performed by Pascoli and Lavendi then revealed linear (N‐terminated) geometries for all the investigated C 2 n −1 N − ( n= 2–4) and C 2 n N − ( n= 1–3) anions with singlet ( 1 Σ + ) and triplet ( 3 Σ − ) ground states, respectively. More recent theoretical investigations of various C n N m species of different spin state and charge support the results of the DFT computations . For C 4 N − , an electronically closed‐shell singlet 1 A 1 excited state with a branched, kite‐like structure of C 2 v symmetry is predicted +15 kJ mol −1 above the 3 Σ − ground state.…”
Section: Introductionsupporting
confidence: 59%
“…The long‐range dispersion‐corrected hybrid density functional ωB97X‐D with Dunning's augmented correlation‐consistent triple‐zeta basis set (aug‐cc‐pVTZ) was used for all geometry optimizations and harmonic frequency calculations . The known geometries were considered as starting points for the geometry optimizations (see the Supporting Information for Cartesian coordinates of the minimum‐energy structures) . To account for anharmonic effects and systematic errors on the harmonic force constants, harmonic frequencies were scaled using a method‐dependent scaling factor of 0.957 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19,28,29,31,32,38−40 Mogren and co-workers found that the lowest energy structures for the C x N y − clusters with (x + y) ≥ 5 and y ≥ 2 were bent or cyclic. 31 The more abundant clusters we observe in this region coincide with these highly stable cyclic structures.…”
Section: Results and Analysismentioning
confidence: 53%
“…Structurally, these clusters are likely linear or bent C x clusters with terminally bound N atoms in the form of CN, that is, they are C (x-1) CN species, as calculated by Mogren et al and seen by others. 28,31,32 In Figure 2b, the signal intensity of the C x N − clusters is diminished, including CN − , but C x N 3 − for x = 2, 3 clusters are observed. The N/C ratio in 2 is 3.6 times higher than the N/C ratio in 1 (Table S1), which presumably accounts for the increased production of multiplynitrogenated clusters upon the ablation of 2.…”
Section: Results and Analysismentioning
confidence: 95%